ASPECTS OF FUNCTIONAL STABILITY IN INFORMATION AND CONTROL SYSTEMS: ASPECTS OF FUNCTIONAL STABILITY IN INFORMATION AND CONTROL SYSTEMS - Chiflidzhanova-Hubenova , Zoya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper presents with the problem of functional stability of the information and control systems. The purpose of the study is the creation of new approach for functional stability of systems of radio-communication systems. The approach suggested will find application in elaborations of systems for professional radio communications with high requirements for verifications of the transmitted information on a complex and difficult environment.